Menangkap Realitas Rakyat dan Kritik terhadap Kolonialisme dalam Lukisan: Sejarah Persagi, 1938-1942 - Yuliana, Alda; Arifin, Faizal (Warisan: Journal of History and Cultural Heritage, 2023)
This research examines the history of establishing Indonesia's first modern art organization, namely the Indonesian Painters Association (Persagi). Persagi is an art organization that influenced the identity of Indonesian art at the end of the Dutch colonial era. of Indonesian art at the end of the Dutch colonial era. This study uses the historical method, which stages: heuristics, verification, interpretation, and historiography. This research utilizes primary historical sources such as Bataviasche Kunstkring, OriÃ«ntatie; Cultureel Maandblad, and Provinciale Zeeuwse Courant. These digital archives include articles, newspapers, and magazines from the Dutch colonial period. The study results show that Persagi tries to find authentic Indonesian styles in painting. Persagi provides a platform for artists to express the reality of indigenous people's lives through their art as a critique of colonialism and the ideological values of "Mooi Indie" (Beautiful Indies) centered on the Netherlands. This research shows that criticism of colonialism is not only limited to organizational and political elites through the study of social history. Exploring this artist community reveals the relationship between art and criticism of social reality, which needs further study.